ASSESSMENT LEVEL OF PHYSICAL ACTIVITY AND PSYCHO-EMOTIONAL HEALTH STATUS OF THE BOGOMOLETS NATIONAL MEDICAL UNIVERSITY STUDENTS UNDER CONDITIONS OF DISTANCE LEARNING ORGANIZATION - Kalashchenko , Svitlana; Луцак , Олена; Hrynzovskyi , Anatolii; Kovalchuk , Oleksandr; Martynenko , Serhii; Kondratiuk , Mykola (The Ukrainian Scientific Medical Youth Journal, 2021)
deterioration of epidemiological situation in the country and educational institutions due to the spread of coronavirus infection prompted the government to change the educational process and move it to distance learning. Psychological support and assistance of future doctors are critical, as, in our country, there is a growing shortage of medical staff, namely doctors, during the COVID-19 pandemic. One way to solve the above problems is to study students of higher medical institutes (SHMI) views on the transition to distance learning, which is essential to identify weaknesses and issues in the higher medical institutions of our country and to purposefully take measures to improve the pedagogical process based on identified needs. The aim of our research includes assessment of the level of physical activity and psycho-emotional health of the higher medical education seekers' of the healthcare field specialty 222 medicine using distance education under quarantine conditions (additional psycho-emotional impact) and establish ways for improving it with a combination of distance education and different psycho-emotional impact. A survey was conducted among 155 Bogomolets National Medical University SHMI of the 1st and 2nd year of study. Developed by us questionnaire have included questions about the assessment of the educational process organization (at the classroom and at "distance"), SHMI routine (work and leisure), namely amount of their spending time for sports and on the gadget use. Significant attention had been given to SHMI assessment of their health, psycho-emotional state, and level of adaptation during the study. During processing results of the motor activity study of surveyed SHMI had been revealed an insufficient level of motor activity. Thus, only 14% of SHMI do morning gymnastics, 29% of respondents go in for sports three times a week. We also found that a significant proportion of respondents have not enough duration of night sleep, which negatively affects the study's success and potentially worsens their health. Analysis of the surveyed SHMI work and rest schedule shows that most SHMI sleep at night on weekdays for 6 to 7 hours (72%). 25% of respondents have a sleep duration of up to 5 hours and only 3% of respondents have slept more than 9 hours. However, chronic insomnia can gradually lead not only to diseases but also to disorders such as, decreasing concentration memory impairment, reduce performance and work efficiency. Significant mental and psycho-emotional overload during distance education requires establishing of physiological day regime. Assessment of the functional state of SHMI allows timely attention and identifies certain risk groups among SHMI. Currently, distance education is developing rapidly due to quarantine restrictions, the rapid development of the Internet, and the constant improvement of communication methods. Therefore, it is essential to improve the effective organization of distance education in terms of providing SHMI with the required level of knowledge and paying due attention to problem issues.